Cosmography and Large Scale Structure by 𝑓(𝑅)-Gravity: New Results - Salvatore Capozziello (Advances in Astronomy, 2009)
The so-called 𝑓(𝑅)-gravity has recently attracted a lot of interest since it could be, in principle, able to explain the accelerated expansion of the Universe without adding unknown forms of dark energy/dark matter but, more simply, extending the General Relativity by generic functions of the Ricci scalar. However, apart several phenomenological models, there is no final 𝑓(𝑅)-theory capable of fitting all the observations and addressing all the issues related to the presence of dark energy and dark matter. An alternative approach could be to “reconstruct” the form of 𝑓(𝑅) starting from data without imposing particular classes of model. Besides, adopting the same philosophy, we take into account the possibility that galaxy cluster masses, estimated at X-ray wavelengths, could be explained, without dark matter, reconstructing the weak-field limit of analytic 𝑓(𝑅) models. The corrected gravitational potential, obtained in this approximation, is used to estimate the total mass of a sample of 12 well-shaped clusters of galaxies.